Assembly of vaccinia virus: incorporation of p14 and p32 into the membrane of the intracellular mature virus. - Sodeik, B (1995)
The cytoplasmic assembly of vaccinia virus begins with the transformation of a two-membraned cisterna derived from the intermediate compartment between the endoplasmic reticulum and the Golgi complex. This cisterna develops into a viral crescent which eventually forms a spherical immature virus (IV) that matures into the intracellular mature virus (IMV). Using immunoelectron microscopy, we determined the subcellular localization of p32 and p14, two membrane-associated proteins of vaccinia virus. p32 was associated with vaccinia virus membranes at all stages of virion assembly, starting with the viral crescents, as well as with the membranes which accumulated during the inhibition of assembly by rifampin. There was also low but significant labelling of membranes of some cellular compartments, especially those in the vicinity of the Golgi complex. In contrast, anti-p14 labelled neither the crescents nor the IV but gave strong labelling of an intermediate form between IV and IMV and was then associated with all later viral forms. This protein was also not significantly detected on identifiable cellular membranes. Both p32 and p14 were abundantly expressed on the surface of intact IMV. Our data are consistent with a model whereby p32 would become inserted into cellular membranes before being incorporated into the crescents whereas p14 would be posttranslationally associated with the viral outer membrane at a specific later stage of the viral life cycle.